ANALISIS PENGARUH PENDIDIKAN DAN JUMLAH TANGGUGAN KELUARGA TERHADAP PARTISIPASI PEREMPUAN DALAM MENGEMBANGKAN USAHA MIKRO(Studi Kasus Jorong Koto Sawah Nagari Ujung Gading Pasaman Barat) - Rahma Yunita; Andis Febrian (Adisam Publisher, 2024)
As for the matter within that is how education and the number of family dependents influence women's desire to set up micro businesses in Jorong Koto Sawah. There are different theories between educational theory and the number of family dependents and what happens in the field. The problem formulation for this research is how much influence education and the number of family dependents have on women's participation in developing micro businesses and the respondents in this research were 40 people. This research is field research with a quantitative approach. The data used in this research is primary data collected through interviews and questionnaires. Data analysis techniques include multiple linear regression analysis, T test, F test and Determination test. Model testing before research, classical assumption testing, and hypothesis testing were carried out with SPSS 23. The results of multiple linear regression research were found using SPSS 23 showing that the regression coefficient for education and also the number of family dependents was positive, indicating that there was a positive and significant relationship between education (X1) and the number of family dependents (X2) on women's participation (Y) in developing micro businesses in Jorong Koto Sawah. The R square value is 521.2%, while the remaining 48.8% is explained by other factors not discussed in the model.